Zygomaticomaxillary complex fracture repair with intraoperative CBCT imaging. A prospective cohort study. Issue 1 (January 2022) - van Hout, W.M.M.T.; de Kort, W.W.B.; ten Harkel, T.C.; Van Cann, E.M.; Rosenberg, A.J.W.P.
Abstract: The aim of this study was to evaluate the value of intraoperative conebeam computed tomography (CBCT) imaging in the treatment of zygomaticomaxillary complex (ZMC) fractures. A prospective single center cohort study was performed. Included were consecutive patients who underwent surgery for a unilateral ZMC fracture. An intraoperative CBCT scan was performed after reduction of the ZMC fracture. Revision reduction was performed of the ZMC and/or orbital floor (OF) on indication. The preoperative and postoperative asymmetry of the outer surface of the ZMC was measured on digital 3D-models of CBCT scans, using a mirroring and surface-based matching technique. The postoperative asymmetry of the ZMC in the study group was compared to the asymmetry of the ZMC in the control group with healthy individuals. A total of 38 patients with a unilateral ZMC fracture were included. The mean postoperative asymmetry in the study group (1.67 mm, SD 0.89) was less than the mean preoperative asymmetry (2.69 mm, SD 0.95) (paired samples T-test p < 0.01) but showed no statistically significant difference with the mean asymmetry in the healthy control group (1.40 mm, SD 0.54) (independent samples T-test p = 0.31). Revision reduction of the ZMC and/or OF fracture had been performed in 11 cases after malalignment was noted on the intraoperative CBCT. The indication for intraoperative revision reduction was associated with comminuted ZMC fractures and/or fractures with indication for OF reduction (Pearson Chi Square p < 0.01). Within the limitations of the study, intraoperative CBCT imaging seemed to have a positive influence on ZMC fracture treatment, especially in the case of comminuted ZMC fractures and/or fractures with indication for OF treatment.